Praksis Seni Pada Sanggar Swargaloka Jakarta Timur Menurut Perspektif Pierre Bourdieu - Sugiarti, Rizky Amelia (Jurnal Pendidikan Tari, 2021)
This research is entitled Praxis of Art at Swargaloka Studio East Jakarta in Pierre Bourdieu's perspective was carried out based on empirical problems in the current field, the dance studio only operates as a place for traditional dance practice. However, Swargaloka Studio shows a difference from other studios in the East Jakarta area. Thus, this study aims to describe the practice of art at the Swargaloka Studio East Jakarta. This study used a qualitative method with a descriptive qualitative approach and analyzed using Bourdieu's theory, such as habitus, capital, and arena. The results of this study showed that habitus, capital, and arena are interrelated to support the practice of art at Swargaloka Studio, this leads to artistic activities that are different from other studios in East Jakarta. In Pierre Bourdieu's perspective, the habitus possessed by Swargaloka Studio is a skill that is achieved through dance training. The economic capital owned is in the form of assets, artistic and educational background as cultural capital, and social relations, both physical and virtual as social capital. The arena where the Swargaloka Studio takes part is the East Jakarta City area and the publication media.